A Review of Disclosure Translation Showing Gender Discrimination and Social Class Discrimination in Novel "Girl from The Coast" - Nunun Tri Widarwati, Ratih Wijayava, Giyatmi (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2021)
The aim of the study are to find Gender discrimination in Novel and acceptability quality of translation from Novel of the girls of the coast. We used methodology of research with descriptive qualitative. The results are 71,43% acceptability of translation quality with score 3 (high) and social discrimination in subordination 62,5%. The benefit of results are to develop literature of translation quality and analysis discrimination aspect in novel of the girls from the coast. The innovation of novelty are teory and guidance of translation in social and gender discrimination with quality translation.